Media KOKELOJO: Transformasi Dan Inovasi Pembelajaran Pendidikan Pancasila Untuk Mengidentifiksi Lingkungan Tempat Tinggal Serta Uji Keefektifan Pada Siswa Kelas IV SD - Bela Dwi Cintiya Sari; Alfi Laila; Farida Nurlaila Zunaidah (STKIP Singkawang, 2026)
This research was conducted to develop an innovative and effective learning media in learning activities using the KOKELOJO (Jombang Local Wisdom Comics) media that can be used by teachers and students in improving the ability to identify residential environments that focus on the value of local wisdom of the residential environment, especially in Jombang Regency which is integrated into the Pancasila Education class IV elementary school learning subjects. The background of this research is based on the low integration of local cultural values and the development of learning media based on local wisdom values that are integrated into learning activities. The type used in this study is that this type of research uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The test subjects amounted to 42 elementary school grade IV students. The data collection technique was carried out at the effectiveness test stage through pretest and posttest tests through a one-group pretest-posttest design. The data analysis technique used is quantitative analysis with N-Gain calculation to find out the improvement in student learning outcomes after using media. The results showed an increase in the average score from the pretest of 67.33 to 84.61 in the posttest, with an N-Gain value of 0.53 which was classified as a medium category. This indicates an improvement in students' cognitive abilities, especially in identifying the living environment with a local cultural value-based approach. Based on these findings, it can be concluded that KOKELOJO media is effectively used in learning Pancasila Education in fostering students' appreciation of the diversity of local cultures in the residential environment.